Synthesis, In Silico Molecular Docking Studies and Antimicrobial Activity of Norfloxacin Schiff Bases - Verma, Stuti; Sharma, Deepak (Asian Journal of Pharmaceutical Research and Development, 2017)
The molecular docking and antimicrobial activity studies of synthesized norfloxacin schiff bases were performed, in order to provide insights into the mechanism of action of potential antimicrobial drugs for resistant microorganisms. antimicrobial activity of compounds was investigated in vitro under aseptic conditions, using the disk diffusion method, against various gram positive and gram negative pathogenic microorganisms such as Pseudomonas aeruginosa (P.A.), Staphylococcus aureus (S. aureus), Helicobacter pylori (H. pylori), Escherichia coli (E. coli), Methicillin-resistant Staphylococcus aureus (MRSA) and some fungal strains such as, Aspergillus fumigatus, Pneumocystis carinii and Aspergillus niger. A series of these compounds were prepared and have been shown to inhibit pathogenic growth, judging from the area of the zone of inhibition. The area of zone of inhibition of compounds found from 6 mm 2 to 48 mm2 . Among the synthesized compounds; compound SV-22 showed good activity against E. coli; Compound SV-23 showed good activity against S.aureus. compounds SV-22, SV-23, SV-24, SV-25, SV-26, SV-27 and SV-28 exhibited promising antibacterial activity against all the selected bacterial strains at 300 µg/ml dose.